Clinical experience of intravenous lacosamide in infants and young children. (March 2016) - Arkilo, Dimitrios; Gustafson, Mary; Ritter, Frank J.
Abstract: Objective: To review our clinical experience with intravenous (iv) lacosamide (LCM) in children less than 12 years old. Background: Use of LCM to treat children with epilepsy has been supported by multiple studies with limited information on iv use in children. Designs/Methods: All children given iv LCM were identified from 2009 to 2015. Records were audited for demographics, seizure classification, etiology, EEG, imaging, indication. Baseline seizure frequency was based on parental reporting, continuous video EEG and direct observation. Results: 47 patients were identified with median age 6.5 years, 18 less than 3 years old, including 8 younger than 12 months. LCM was an adjunctive therapy of ≥2 antiepileptic drugs (AEDs). LCM was administered intravenously to treat epilepsia partialis continua (n = 3, dose range 5–10 mg/kg), status epilepticus (n = 11, median dose 7.2 mg/kg, range 4–11 mg/kg), and acute exacerbation of seizure frequency (n = 18, median dose 4.5 mg/kg, range 1–11 mg/kg). Parenteral form was substituted for oral form for 10 children treated with maintenance LCM unable to ingest/tolerate enteral medication and 5 who were given iv LCM to initiate maintenance treatment (median dose 4 mg/kg, range: 2–10 mg/kg). The infusion was effective for 24 out of 37 children (65%) naive to LCM. Sedation (one with ataxia) was noted in 5/36 children (14%), without any other identified adverse events. Conclusion: This is the first published retrospective study of very young critically ill children receiving iv LCM. The acute tolerability at this dosing range represents a positive trend and need confirmation from larger studies. Highlights: Response to iv lacosamide was evaluated in children less than 12 years of age. 47 children were identified, 18 less than 3 years old, 8 infants (dose 2–11 mg/kg). Response included cessation or greater than 50% reduction of baseline seizures. The retrospective review suggested good response to treatment in 2/3 of cases. Initial doses of lacosamide ranged from 2 to 11 mg/kg.